Development external quality assessment utilization model for improving internal quality assurance system of the child development center - Treekom Prommaboon; Siriluck Boongthong; Krit Pinthong; Piyaporn Seesun; Prasart Nuangchalerm (International Journal of Evaluation and Research in Education (IJERE), 2026)
This research focuses on the development of an external quality assessment (EQA) utilization model for enhancing the internal quality assurance system within child development centers. The research employed research and development (R&D) methods along with parallel mixed methods, the study unfolds in three distinct phases. Phase 1 involves a comprehensive survey of current conditions, problems, needs, participation, and the utilization of EQA in developing the internal quality assurance system of child development centers. Phase 2 constitutes a multiple-case study, employing in-depth interviews for data collection. Phase 3 integrates findings from phases 1 and 2 to synthesize a model for utilizing test results. Finally, the study involves the trial and evaluation of practice guidelines employing EQA utilization to improve the internal quality assurance system. The findings indicate that the current conditions of quality assurance operations in child development centers under local administrative organizations are mostly complete but exhibit problems at a low level across all standards. Organizational commitment, participation in internal quality assurance operations, adaptation from external assessment results, and attitude towards quality assurance are crucial contributors. In conclusion, the EQA utilization model for improving the internal quality assurance system of the child development center as a practical and effective tool for enhancing quality assurance processes.